Identification of a giant mediastinal teratoma by echocardiography: A case report. Issue 6 (11th January 2019) - Xiao‐dong, Li; Li, Zhang; Xiu‐mei, Duan; Ming‐bo, Tang; Xiao‐cong, Wang
Abstract: The diagnosis of mediastinal space‐occupying lesions largely relies on X‐ray and computed tomography. However, thanks to technological progress, transthoracic echocardiography can clearly display the mediastinal structures surrounding the heart and great vessels, thereby improving the detection rate of mediastinal space‐occupying lesions. Primary mediastinal teratoma is relatively rare, and removal of giant mediastinal teratoma by thoracoscopic surgery has rarely been reported. Here, we report a case of giant mediastinal teratoma diagnosed by transthoracic echocardiography, which was treated by complete thoracoscopic resection and confirmed by histology.